PENGARUH MEDIA KINTAR TERHADAP KEMAMPUAN KEAKSARAAN AWAL ANAK USIA 5-6 TAHUN DI TK TUNAS REMAJA SURABAYA - Utari Safitri; Aisyah Aisyah; Ervin Nurul Affrida (incrementapedia, 2022)
This research is motivate by the problem that the early literacy abilitie of children age 5-6 years are still not developed. This is because the teacher only uses the lack of media, namely teaching materials for children's worksheets, so that children feel bored and less enthusiastic. Therefore, researchers make creative media, namely KINTAR media (Kincir Pintar). Media KINTAR (Kintar Pintar) is a game media that is made to resemble a windmill made of plywood or wood with the symbol of the letters (a)  to (z) in various colors and attractively decorated. The motivation of this study was to determine the effect of KINTAR media on the early skills of children aged 5-6 year in TK Tunas Remaja Surabaya. The exam strategy used is a quantitative exploration technique with the design of "One Group Pretest Posttest Design", the T-test using the SPSS version 24 application. The sample in this study was 25 children aged 5-6 years at Tunas Remaja Surabaya Kindergarten. The information sorting strategy used is the perception technique and documentation. Base on the result of the paired sample test using the SPSS version 24 application, it shows that from the calculation results above, it is obtained sig (2- tailed) 0.000 < 0.05, then at that time Ho is reject so that the working hypothesis is very significant. Thus, its can be stated that the KINTAR media hasa tremendous impact on early proficiency abilites of childrens age 5-6 years at Tunas Remaja Surabaya Kindergarten.